The Effect of Green Technology Innovation on Financial Performance in Manufacturing Companies Listed on the Indonesia Stock Exchange - Sri Nurdiyanti; Susi Sarumpaet (International Journal of Economics, Management and Accounting, 2024)
This study was conducted with the aim of examining the effect of green process innovation variables and green product innovation on the company's financial performance with total asset turnover variables as control variables. The dance used in this selection is the Resource Based View (RBV) theory and stakeholder theory. The population used in the study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. Sampling was carried out using purposive sampling technique. The number of samples used in this assessment was 400 samples. The results of this study indicate that green process innovation and green product innovation have a positive and significant effect on corporate financial performance. The results of this study also found that the control variable of total asset turnover is able to control the effect of green process innovation and green product innovation on corporate financial performance.